Electric stimulation of the right temporo-parietal junction induces a task-specific effect in deceptive behaviors - Noguchi, Yasuki; Oizumi, Rei (Neuroscience research, 2018)
•We applied anodal tDCS when subjects aimed to deceive another person.•The tDCS to the right temporo-parietal junction reduced a success rate of deception.•This tDCS effect was specific to a task in which subjects stated their false opinions. How the brain generates a lie is an important and unsolved issue in neuroscience. Previous studies indicated that mentalizing, the ability to understand and manipulate the mental states of others, plays a critical role in successful deception. Accordingly, recent neuroimaging studies reported deception-related activity in the right temporo-parietal junction (rTPJ), a brain region closely related to the mentalizing ability. Detailed functions of rTPJ in deception, however, remain unclear. In the present study, we investigated a causal relationship between rTPJ and deception using transcranial direct-current stimulation (tDCS). Subjects received anodal tDCS to their rTPJ or V1 (control) and then performed three tasks in which they aimed to deceive another participant to get monetary rewards. In one of the three tasks, we found a significant decrease in a rate of successful deception when rTPJ was stimulated, indicating that neural enhancement of rTPJ caused poorer (not better) deceptive performances. Our results suggest that, in some tasks involving selfish (money-motivated) lying, neural processing in rTPJ does not contribute to successful deception through the metalizing ability. Rather, it would be related to the self-monitoring of morally-unacceptable behaviors (lying). The neural enhancement of rTPJ therefore increased the psychological resistance to lying, resulting in poorer deceptive performances.